"Not performing worse but feeling older !" the negative effect of the induction of a negative aging stereotype. (November 2020) - Deshayes, Maxime; Clément-Guillotin, Corentin; Chorin, Frédéric; Guérin, Olivier; Zory, Raphaël
Abstract: The present research investigated the effect of the induction of a negative stereotype on older adults' performance during an endurance task, and how this stereotype influenced older adults' subjective age. Thirty-four old women were randomly assigned to one of the two conditions: a negative stereotype condition and a nullified-stereotype condition. They performed an endurance task consisting of maintaining 30% of their maximal strength, as long as possible. Then, they answered a questionnaire including subjective age measurement. Contrary to expectations, the induction of the negative stereotype did not influence participants' endurance performance. However, participants in the negative stereotype condition felt older than participants in the nullified-stereotype condition. As subjective age is relevant to late-life health outcomes, such as walking speed or mortality risk, it seems necessary to implement some strategies to decrease the negative effect of the negative stereotype on subjective age. Highlights: Negative aging stereotypes do not influence endurance performance. Older adults would react differently than other groups in a threat situation. Negative aging stereotypes negatively influence subjective age.